Temperature and consumer type dependencies of energy flows in natural communities - Lang, Birgit; Ehnes, Roswitha B.; Brose, Ulrich; Rall, Björn C. (Oikos, 2017)
With the world continuously warming, a mechanistic understanding of how temperature affects interaction strengths, which are fundamental to food-web stability, is needed. As interaction strengths are determined by the flows of energy from resources to consumers, we investigated effects of temperature on animal energetics. We used newly compiled datasets on respiration rates and assimilation efficiencies to assess how temperature affects the energy use (respiration rates) and the efficiency of energy gain (assimilation efficiency) for different consumer types. Furthermore, we incorporated our findings in a simulation of temperature effects on maintenance feeding rates (i.e. energy consumption necessary to sustain life). Our analysis revealed a generally positive temperature dependence of assimilation efficiencies across consumer types thus implying a net energy gain with warming. The temperature scaling of respiration rates did not differ between consumer types. Based on these parameters we calculated maintenance feeding rates and compared them to empirically measured (realized) feeding rates. This comparison revealed that detritivores and herbivores have the potential to increase their biomasses under warming as their maintenance feeding rates increase less strongly than their realized feeding rates. For carnivores, however, we found a stronger increase of their maintenance feeding rates compared to their realized feeding rates, which should lead to decreased population sizes under warming. Overall, our results increase the understanding of climate change effects on ecosystems as they suggest profound energetic consequences for natural communities.